The Relationship of Exposure to Plastic Food and Beverage Packaging on The Severity Stadium of Endometriosis at Dr. Soetomo General Hospital Surabaya - Zafirah Delia; Sri Ratna Dwiningsih; Pudji Lestari (PROFESSIONAL HEALTH JOURNAL, 2025)
Introduction: Endometriosis is a gynecological problem which is one of the main causes of secondary dysmenorrhea with pathological conditions. Endometriosis is defined as a disorder characterized by the presence of tissue similar to the endometrial layer growing outside the uterus which occurs in women of reproductive age. Bisphenol A (BPA) and phthalates are two substances found in food and beverage plastics that may be endocrine disrupting chemicals (EDC). Hormonal system abnormalities are intimately linked to endometriosis. Objectives: This study aims to prove the relationship between exposure to food and drink plastic and the stage of endometriosis. Methods: The design of this research is observational analytics with a retrospective approach. The sampling technique used non-probability sampling with a consecutive sampling approach of 96 respondents. Data analysis used the chi square test. Results: The research results showed that 65.63% (63) of respondents experienced moderate levels of exposure to plastic food and drinks. As many as 34.38% (33) of respondents experienced stage IV (severe) endometriosis. The results of the correlation between exposure to plastic food and drinks and the stage of endometriosis showed p value = 0.042. Conclusions: There is a significant relationship between exposure to food and drink plastic and the stage of endometriosis at Dr. Soetomo General Hospital Surabaya